Hop Test Performance is Associated with Return-to-Sport but Shows Limited Association with Reinjury after Anterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-Analysis - Yiyan Liu; Yuxin Sun; Mingde Cao; Dan Wang; Lin Wang; Daniel T.P. Fong; Patrick Shu-Hang Yung; Jihong Qiu (Journal of Sports Science and Medicine, 2026)
Hop tests are commonly used to assess return to sports (RTS) after anterior cruciate ligament reconstruction (ACLR), yet whether they can effectively predict successful RTS and reinjury risk remains unclear. This systematic review and meta-analysis aimed to determine the associations between hop test performance and the likelihood of RTS and reinjury following ACLR. PubMed, SPORTDiscus with Full Text, MEDLINE and Web of Science were searched for studies that included participants with primary unilateral ACLR, assessed functional performance using hop tests and reported outcomes of RTS and reinjury. Data on participant characteristics, follow-up duration, RTS criteria, hop test types and measures, and relevant results were extracted. Data were synthesized using quantitative or qualitative approaches. Risk of bias was assessed using a modified Newcastle-Ottawa Scale, and the quality of evidence was evaluated with the modified GRADE framework. Forty-three studies involving 17, 350 participants were included. Twenty-four studies investigated RTS and 21 examined reinjury. Meta-analyses revealed achieving a limb symmetry index (LSI) ≥ 90% in single-leg hop for distance (SLHD) (OR = 1.20, 95% CI: 1.09 to 1.33) or triple crossover hop for distance (TCHD) (OR = 1.18, 95% CI: 1.02 to 1.36) was associated with a higher probability of RTS, whereas achieving LSI ≥ 90% in triple hop for distance (OR = 1.05, 95% CI: 1.01 to 1.09) was associated with increased odds of reinjury. Subgroup analyses showed stronger associations for RTS in studies with > 90% hamstring tendon autografts (OR = 1.64, 95% CI: 1.13 to 2.39) and among individuals without meniscal injury (OR = 1.39, 95% CI: 1.14 to 1.69). Overall, low certainty of evidence suggests achieving an LSI ≥ 90% in SLHD and TCHD is associated with a higher likelihood of RTS within two years after ACLR, particularly in individuals with hamstring autografts and without meniscal injury. However, distance-based performance of hop test alone may be insufficient to predict reinjury risk.